Influence of e-learning on secondary school students’ moral values and academic achievement in two local government areas in Ondo State (2009)
Electronic media can make learning realistic and lively by motivating and generating interest in learning. Educational media as it is often called also facilitates and promotes assimilation and retention of facts, it can equally be abused which can result in poor academic performance and moral vices among students. This paper employed a survey design with a single- type questionnaire that showed the influence of electronic media on students’ moral development and academic performance. The data collected was analyzed using a descriptive statistics of frequency count and percentages. Findings show that electronic media have negative influence on students’ moral development and academic performance. Hence, parents and teachers have to guide students’ use of electronic media for the purposes of information, education and even entertainment.